The amplitude of the kilohertz quasi-periodic oscillations in 4U 1728-34, 4U 1608-52, and aquila X-1, as a function of X-ray intensity - Méndez, Mariano R. (2001)
We study the kilohertz quasi-periodic oscillations (kHz QPOs) in the low-mass X-ray binaries 4U 1728-34, 4U 1608-52, and Aq1 X-1. Each source traces out a set of nearly parallel tracks in a frequency versus X-ray count rate diagram. We find that between two of these tracks, for similar QPO frequency, the 2-60 keV source count rate can differ by up to a factor of ∼4, whereas at the same time the rms amplitude of the kHz QPOs is only a factor of ∼1.1 different. We also find that, for 4U 1608-52 and Aq1 X-1, the rms spectrum of the kHz QPOs does not depend upon which track the source occupies in the frequency versus X-ray count rate diagram. Our results for 4U 1728-34, 4U 1608-52, and Aq1 X-1 are inconsistent with simple "extra source of X-rays" scenarios for the parallel tracks, such as those in which the properties of the kHz QPOs are determined only by the mass accretion rate through the disk, whereas X-ray count rate also depends upon other sources of energy that do not affect the QPOs.